Celebrity Endorsed Advertisements and Its Influence on Brand Choice and Buying Behavior of Females - Dr. Abdul Rehman Qaisar; Dr. Bakht Rawan; Dr. Muhammad Sher Juni (National University of Modern Languages (NUML), Islamabad, 2022)
Celebrity endorsement is considered one of the popular tools of marketing which is used by many brands. The purpose is to involve any famous celebrity in order to promote that specific brand. Present study is designed to explore influence of celebrity endorsed advertisements on brand choice and perception of female students. Using survey research design, data from 300 female respondents is collected through a well-designed questionnaire.  Theoretically, present study is based on elaboration likelihood model. In order to draw inferences from collected data, statistical tests such as chi square and correlation are used. Overall analysis describes that advertising has significant impact on brand choice of female students. Results also indicate that female students give more attention to advertisement of cosmetics and dresses as compared to gadgets. Accordingly, comparative analysis of the selected mediums for advertising showed that overall female students more prefer social media as compared to TV and print media for acquiring information about products and brands. Findings also suggest that celebrity is one of the key factors in advertising to influence females brand choices. It is evident from the findings that females are increasingly becoming brand conscious due to the role of celebrities which is part of celebrity endorsement. Brands advertisements containing celebrities have more successful impact as compared to brand ads without celebrities.